Structural and biophysical studies of RNA-dependent RNA polymerases - Wright, S (2010)
RNA-dependent RNA polymerases (RdRps) play a vital role in the life cycle of RNA viruses, being responsible for genome replication and mRNA transcription. In this thesis viral RdRps (vRdRps) of dsRNA bacteriophage phi6 (phi6 RdRp) and Severe Acute Respiratory Syndrome (SARS) coronavirus [non structural protein 12 (NSP-12)] are studied. For SARS polymerase NSP-12, a library-based screening method known as ESPRIT (Expression of Soluble Protein by Random Incremental Truncation) was employed in an attempt to isolate domains of NSP-12 that express solubly in Escherichia coli (E. coli) and are thereby suitable for structural studies. This experiment identified for the first time in a systematic fashion, conditions under which the SARS polymerase could be solubly expressed at small scale and allowed mapping of domain boundaries. Further experiments explored different approaches for increasing expression levels of tractable fragments at large scale. Bacteriophage phi6 RdRp is one of the best studied vRdRps. It initiates RNA synthesis using a de novo mechanism without the need for a primer. Although formation of the de novo initiation complex has been well studied, little is known about the mechanism for the transition from initiation to elongation (i.e. extension of an initiated dinucleotide daughter strand). In the phi6 RdRp initiation complex the C-terminal domain (CTD) blocks the exit path of the newly synthesised dsRNA which must be displaced for the addition of the third nucleotide. The crystal structure of a C-terminally truncated phi6 RdRp (P2T1) reveals the strong non-covalent interactions between the CTD and the main body of the polymerase that must be overcome for the elongation reaction to proceed. Comparing new crystal structures of complexes of both wild-type (WT) and a mutant RdRp (E634 to Q, which removes a salt-bridge between the CTD and main body of the polymerase) with various oligonucleotides (linear and hairpin), nucleoside triphosphates (NTPs) and divalent cations, alongside their biophysical and biochemical properties, provides an insight into the precise molecular details of the transition reaction. Thermal denaturation experiments reveal that Mn2+ acquired from the cell and bound at the phi6 RdRp non-catalytic ion site sufficiently weakens the polymerase structure to facilitate the displacement of the CTD. Our crystallographic and biochemical data also indicate that Mn2+ is released during this displacement and must be replaced for the elongation to proceed. Our data explain the role of the non-catalytic divalent cation in vRdRps and pinpoint the Mn2+-dependent step in viral replication. In addition, by inserting a dysfunctional Mg2+ at the non-catalytic ion site for both WT and E634Q RdRps we captured structures with two NTPs bound within the active site in the absence of Watson-Crick base pairing with template and could map movements of divalent cations during preinitiation through to initiation. Oligonucleotides present on the surface of phi6 RdRp allowed mapping of key residues involved in template entry and unwinding of dsRNA; these preinitiation stages have not been observed previously. Considering the high structural homology of phi6 RdRp with other vRdRps, particularly from (+)ssRNA hepatitis C virus (HCV), insights into the mechanistic and structural details of phi6 RdRp are thought to be relevant to the general understanding of vRdRps.